Designing of Information System for Stock Management using the FAST (FRAMEWORK FOR THE APPLICATIONS) Method - Agustinus Fritz Wijaya; Resa Saputri; Christ Rudianto; Augie David Manuputty (Journal of Information System and Informatics, 2020)
The use of information technology system in managing data of various company activities, especially in the warehouse, is an important part for every company. From the observation that have been made, the information system for recording goods flow in PT Global Infotech Solution is still done manually. During this time, employees carry out the process of recording data of goods at the warehouse using paper, so that the risk of data loss is easily caused by tearing, wet or tucked with other data. The system development method that used is the FAST (Framework for Application System Thinking) Method. This study aims to design an information system for recording goods flow which is expected to make it easier for employees to record goods in the warehouse. Using a computerized system can shorten the time and protect all data items from the risk of theft. The result of this study is designing an information system for recording goods in the form of information systems using the Unified Modeling Language and User Interface. This item recording information system is expected to be able to change the process from a manual recording system to a computerized recording system, so that it can speed up every recording process and minimize the possibility of mistakes in entering the data of goods in the warehouse.